2014
DOI: 10.2108/zs140088
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Epilachna, Henosepilachna, and Some Minor Genera of Phytophagous Ladybird Beetles (Coleoptera: Coccinellidae: Coccinellinae: Epilachnini), with an Analysis of Ancestral Biogeography and Host-Plant Utilization

Abstract: Ladybird beetles in the tribe Epilachnini include notorious crop pests and model species studied intensively in various fields of evolutionary biology. From a combined dataset of mitochondrial (ND2) and nuclear (28S) DNA sequences, we reconstructed the phylogeny of 46 species of Epilachnini from Asia, Africa, America, and the Australian region: 16 species in Epilachna, 24 species in Henosepilachna, and one species each in Adira, Afidenta, Afidentula, Afissula, Chnootriba, and Epiverta. In our phylogenetic tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
(61 reference statements)
1
13
0
1
Order By: Relevance
“…) resembles closely the situation in the congeneric Solanaceae‐feeder H. diffinis (Eydoux et Souleyet) (Kikuta et al ), our recent survey revealed that adults of several other congeneric Solanaceae‐feeders distributed in southeastern Asia also slightly accept centro for feeding (Fujiyama et al ., unpublished data in 2011–2013). This implies the slight ability to use centro had been acquired in the ancestor of the Solanaceae‐feeding clade (Katoh et al ; see also discussion in Kikuta et al ). Moreover, possible sharing of the same gene(s) with other taxonomically and phylogenetically remote legume‐specialists that sporadically occur among epilachnines, such as H. signatipennis (Boisduval), the Mexican bean beetle Epilachna varivestis Mulsant, and Afidenta misella Weise (Katoh et al ), should also be considered to elucidate the origin of the ability of H. vigintioctopunctata to use centro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) resembles closely the situation in the congeneric Solanaceae‐feeder H. diffinis (Eydoux et Souleyet) (Kikuta et al ), our recent survey revealed that adults of several other congeneric Solanaceae‐feeders distributed in southeastern Asia also slightly accept centro for feeding (Fujiyama et al ., unpublished data in 2011–2013). This implies the slight ability to use centro had been acquired in the ancestor of the Solanaceae‐feeding clade (Katoh et al ; see also discussion in Kikuta et al ). Moreover, possible sharing of the same gene(s) with other taxonomically and phylogenetically remote legume‐specialists that sporadically occur among epilachnines, such as H. signatipennis (Boisduval), the Mexican bean beetle Epilachna varivestis Mulsant, and Afidenta misella Weise (Katoh et al ), should also be considered to elucidate the origin of the ability of H. vigintioctopunctata to use centro.…”
Section: Discussionmentioning
confidence: 99%
“…This implies the slight ability to use centro had been acquired in the ancestor of the Solanaceae‐feeding clade (Katoh et al ; see also discussion in Kikuta et al ). Moreover, possible sharing of the same gene(s) with other taxonomically and phylogenetically remote legume‐specialists that sporadically occur among epilachnines, such as H. signatipennis (Boisduval), the Mexican bean beetle Epilachna varivestis Mulsant, and Afidenta misella Weise (Katoh et al ), should also be considered to elucidate the origin of the ability of H. vigintioctopunctata to use centro.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctiveness of the two genera is one of the most controversial subjects in Epilachnini (Pang et al, 2012;Tomaszewska & Szawaryn, 2016). Recent phylogenetic studies including a wide representation of Epilachnini species have shown that both Epilachna and Henosepilachna are polyphyletic (Katoh et al, 2014;Szawaryn et al, 2015). Katoh et al (2014) have reported that three groups of species of Epilachnini cluster together in well-supported clades: Asian Epilachna, American Epilachna and Asian-Australian Henosepilachna.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained by Katoh et al (2014) suggest that Henosepilachna and Epilachna are polyphyletic but also the existence of some well-supported clades, such as Asian Epilachna , American Epilachna and Asian and Australian Henosepilachna . Despite this, Katoh et al (2014) recommended that a new phylogenetic analysis has to be done, with special careful attention to both morphological and molecular analyses with a broad taxonomic representation. Thereby the taxonomy of the species belonging to the genus Henosepilachna remains unclear with misidentification for some species.…”
Section: Introductionmentioning
confidence: 89%
“…Recently Katoh et al (2014) by using a combined dataset of NADH dehydrogenase subunit 2 (ND2) and the 28S rDNA reconstructed the phylogeny of 46 species of Epilachnini , including 16 species of Epilachna and 24 species of Henosepilachna . The results obtained by Katoh et al (2014) suggest that Henosepilachna and Epilachna are polyphyletic but also the existence of some well-supported clades, such as Asian Epilachna , American Epilachna and Asian and Australian Henosepilachna . Despite this, Katoh et al (2014) recommended that a new phylogenetic analysis has to be done, with special careful attention to both morphological and molecular analyses with a broad taxonomic representation.…”
Section: Introductionmentioning
confidence: 99%